The impact of Proactiveness and analysis strategic orientation tax organizational excellence: Practical research in the General Authority for Taxes (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This research aims to show the nature of the impact of proactive and analytical strategic orientation in the dimensions of tax organizational excellence (leadership, strategic planning, information and analysis and knowledge management, focus on taxpayers, focus on operations, focus on workforce, business results), in the General Tax Authority  The questionnaire was used as a tool to collect data and information from the sample of (110) who are (Associate Director General, Head of Department, Under-Head of First Division, Under-Head of Second Section, Division Officer).  Arithmetic mean, intestinal deviation the research has reached a number of conclusions, the most prominent of which are: -• There is an effect of proactive and analytical strategic orientation in the dimensions of tax regulatory superiority,• There are no differences in the sample response about Questionnaire items according to personal variables (educational attainment, job position, and years of service).